8
$\begingroup$

When I want to calculate $$\int{\frac {x^2}{ ( x\cos x -\sin x ) ^2}}\,{\rm d}x$$ I have tested with software and get $${\frac {x\sin \left( x \right) +\cos \left( x \right) }{x\cos \left( x \right) -\sin \left( x \right) }}$$

But I can not come to this conclusion, neither using integration by parts, nor using trigonometric identities, nor multiplying by their conjugate, Even by rational trigonometric substitution. I do not know what else to try. Could you give me any suggestions?

$\endgroup$
8
$\begingroup$

We can rewrite $$\begin{align}\int \frac{x^2}{(\sin x - x\cos x)^2} \, \mathrm{d}x &= \int \frac{x\sin x(x\sin x + \cos x)}{(\sin x - x\cos x)^2} \, \mathrm{d}x - \int \frac{x\cos x}{\sin x - x\cos x} \, \mathrm{d}x \\ & = -\frac{x\sin x + \cos x}{\sin x - x\cos x} \color{green}{+} \int \frac{x\cos x}{\sin x- x\cos x} \, \mathrm{d}x \color{red}{-} \int \frac{x\cos x}{\sin x - x\cos x} \, \mathrm{d}x \\ & = -\frac{x\sin x + \cos x}{\sin x - x\cos x}\end{align}$$

via IBP with $u = x\sin x + \cos x \implies u' = x\cos x$ and $$\mathrm{d}v = \frac{x\sin x}{(\sin x - x\cos x)^2} \implies v = -\frac{1}{\sin x -x\cos x}$$ via straightforward $f = \sin x - x\cos x \implies f' = x\sin x$ sub.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.